(untitled) (Journal of Geography and Environmental Management, 2019)
Factors of strategic matrix of Kazakhstan are considered and estimation of contribution components in state development is given. It is offered to consider risks of destabilization system at a complex estimation of interaction objects of the natural, social, economic environment.